2007
DOI: 10.2105/ajph.2005.065268
|View full text |Cite
|
Sign up to set email alerts
|

A National Survey of Tobacco Cessation Programs for Youths

Abstract: There is considerable homogeneity among community-based tobacco cessation programs for youths. Programs are least prevalent in the types of communities for which national data show increases in youths' smoking prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 21 publications
1
49
0
2
Order By: Relevance
“…20 Enhancing the potential applicability of our findings, a study found N-O-T to be the most widely used teen smoking intervention in the nation. 21 …”
mentioning
confidence: 99%
“…20 Enhancing the potential applicability of our findings, a study found N-O-T to be the most widely used teen smoking intervention in the nation. 21 …”
mentioning
confidence: 99%
“…Higher education level generally indicates higher socioeconomic status, different social norms, and more knowledge about health risk behaviors, which are consistently associated with lower rates of smoking (3,10). Factors associated with higher smoking prevalence in rural populations include disparities in tobacco control programs and resources, adoption of smoke-free policies, sociodemographic characteristics such as lower income and educational attainment, lower health insurance coverage and reduced access to treatment services, and targeted marketing by the tobacco industry (3,10,(21)(22)(23)(24). Higher smoking rates in urban areas have been attributed to higher levels of stress from living in urban areas (4,5,7,20).…”
Section: Discussionmentioning
confidence: 99%
“…Our study results clearly indicate a need for a population-specific tobacco control approach that addresses the lifestyle, behavior, and education of disparate populations within California in order to lower the higher than average smoking prevalence in such settings. Enforcement of the loosely implemented smoke free laws, education at an early age in schools, the use of multimedia and social network applications, and providing resources for quitting that are culturally in tune with rural communities are some examples of such a multipronged approach (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…A avaliação dos programas de prevenção do tabagismo em adolescentes adotados em alguns países também não tem apresentados resultados satisfatórios, pois observa-se aumento da prevalência do tabagismo entre os jovens 18 (B).…”
Section: O Tratamento Farmacológico Do Tabagismo Deve Ser Diferente Eunclassified